Genetic and molecular insights into tiller development and approaches for crop yield improvement - Chachar, Zaid; Xue, Xiaoming; Fang, Junteng; Chen, Ming; Chen, Weiwei; Li, Xuhui; Ahmed, Nazir; Chachar, Sadaruddin; Ali, Aamir; Chen, Zhong liang; Fan, Lina; Lai, Ruiqiang; et al. (Frontiers in Plant Science, 2025)
Tiller development is a critical factor in boosting agricultural productivity and securing global food security. This review offers a comprehensive analysis of recent advancements in enhancing crop yield through extensive research on tiller development, utilizing a multi-faceted approach that includes quantitative trait loci (QTL) mapping, association studies, and transcriptome analysis across various crops. Extensive investigations have revealed complex genetic, molecular, and environmental interactions that influence this pivotal yield determinant. QTL mapping has pinpointed specific genomic regions associated with tiller development, while genome-wide association studies (GWAS) have provided deeper insights into natural genetic variations within populations. Additionally, transcriptome analyses have offered a dynamic view of gene expression, shedding light on molecular regulatory mechanisms that govern tillering. The integration of these multi-omics approaches has enabled a holistic understanding of the process, identifying crucial genetic loci and expression patterns that are key to optimizing tillering. Key genes such as TaMAX1, TaMOC1, and TN1 in wheat, ZmTB1, ZmD14, and ZmMOC1 in maize, along with MAX1-like genes, OsMAX1, and OsHAM2 in rice have been highlighted. Similar studies in sugarcane have identified genes like SoMAX2, SoMAX3, SoMAX4-1, SoMAX4-2, and SoTB1, which regulate bud outgrowth and tillering. Including involving hormonal control integrates pathway auxins, gibberellins, and cytokinins, to coordinate plant responses to internal and external stimuli “These” discoveries are essential for breeding and genetic engineering strategies aimed at developing crop varieties with favorable tillering traits, ultimately enhancing yield potential.